2014
DOI: 10.2106/jbjs.l.01406
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Continued Opioid Use One to Two Months After Surgery for Musculoskeletal Trauma

Abstract: Patients who continue to use opioid pain medication one to two months after surgery for musculoskeletal trauma have more psychological distress, less effective coping strategies, and greater symptoms and disability than patients who do not take opioids, irrespective of injury, surgical procedure, or surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
186
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(200 citation statements)
references
References 39 publications
9
186
5
Order By: Relevance
“…Although functional outcomes were not assessed in our study, the greater need for posthospitalization care could further be interpreted as a less rapid return of independent functional mobility in this patient population [38,39]. It is possible that lower levels of selfefficacy for managing pain-greater pain catastrophizingand resilience in maintaining function among chronic opioid users contributed to the higher rate of posthospitalization care observed in our study [26,47], and also may partly explain why these patients tend to have worse functional outcomes after orthopaedic procedures [31,32,42,57].…”
Section: Discussionmentioning
confidence: 73%
“…Although functional outcomes were not assessed in our study, the greater need for posthospitalization care could further be interpreted as a less rapid return of independent functional mobility in this patient population [38,39]. It is possible that lower levels of selfefficacy for managing pain-greater pain catastrophizingand resilience in maintaining function among chronic opioid users contributed to the higher rate of posthospitalization care observed in our study [26,47], and also may partly explain why these patients tend to have worse functional outcomes after orthopaedic procedures [31,32,42,57].…”
Section: Discussionmentioning
confidence: 73%
“…Recently, Noiseux et al [19] showed a correlation between preoperative depression and moderate to severe pain with ROM after TKA at 6-month followup. Furthermore, patients with higher scores for catastrophic thinking, anxiety, posttraumatic stress disorder, and depression on several questionnaires are more likely to be taking opioid pain medications 1 to 2 months after musculoskeletal trauma than patients with lower scores [10]. Depression has also been associated with lower baseline and posttreatment MHQ scores in a general population of patients receiving treatment for atraumatic hand conditions [15].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for a higher opioid consumption in men is unclear and might be related to a difference in effectiveness [22] but is also ascribed to sex differences in fear of addiction, previous pain experience, and tolerance to postoperative pain and opioid side effects [20]. A previous study found that the main factor associated with opioid use 1 to 2 months after musculoskeletal trauma was greater catastrophic thinking [7]. We did not find an effect of catastrophic thinking on second opioid prescriptions after distal radius fracture surgery, perhaps because the surgeons involved are quite strict with opioids and tend to identify and coach catastrophic thinking.…”
Section: Discussionmentioning
confidence: 99%
“…postoperative opioid use and psychological factors, catastrophic thinking, and health anxiety in particular [7,8].…”
Section: Introductionmentioning
confidence: 99%